(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
CONTEXTUALIZATION The inclusion of women in the Brazilian labor market occurred gradually and has been marked by structural inequalities. In the public sector, these asymmetries are expressed through the burden of the double workday and the persistence of gender stereotypes, which contribute to the sexual division of labor. The 1995 State Reform, by introducing a managerial logic, intensified the pressure for goals and productivity, increasing the daily tensions faced by female public servants. OBJECTIVE To analyze the reality of Brazilian female public servants from the intersection of gender and work, identifying how structural inequalities and managerialism affect their professional and personal experiences. METHODOLOGY This is qualitative research based on a critical literature review, articulating feminist theories, studies on the Brazilian State, and relevant legislation. RESULTS It was found that the managerial logic increased the productivity demands placed on female public servants without providing the necessary material support. The combination of institutional hierarchy, gender stereotypes, inequality in the division of labor, and social devaluation exacerbates overload, compromising the mental health, quality of life, and professional identity of these workers. CONCLUSION It is concluded that, despite legal advances and the growing presence of women in the labor market, obstacles to gender equality persist. Addressing these inequalities requires institutional policies of equity and appreciation, articulated through an intersectional perspective that considers race, class, and territory. Key-words:1. Civil servant 2. Gender 3. Double shift 4. Managerialism